“Think Globally, Act Ethically”: Towards Normative Assessment of Fertility Tourism Regulation in Europe - Ireni-Saban, Liza; Korkut, Umut; Herzberg, Ben (International Journal of Humanities and Social Science Research, 2016)
In recent years, cross-border reproductive care has become an industry built on reproductive solutions for infertile individuals and couples as well as same sex couples who leave their “home” country to receive fertility treatments abroad. The diverse national policies and regulations across Europe in the field of assisted reproduction represent politically negotiated rationing criteria in states' health policy decisions. This highly diversified regulatory field opens up a range of transnational ethical issues arising from the adverse consequences and concerns of reproductive services and treatments operating across national boundaries. In this paper, we propose to broaden the scope of the EU's normative power to include the adverse consequences and concerns of cross-border travel to seek reproductive care. Towards this end, greater investment in accountability mechanisms should be applied at the EU level to equity issues arising from fertility tourism and to assessing the normative appropriateness of policy responses at both state and supranational levels across Europe to guide regulation in this policy domain.